2020
DOI: 10.1073/pnas.2006379117
|View full text |Cite
|
Sign up to set email alerts
|

Niche expansion for phototrophic sulfur bacteria at the Proterozoic–Phanerozoic transition

Abstract: Fossilized carotenoid hydrocarbons provide a window into the physiology and biochemistry of ancient microbial phototrophic communities for which only a sparse and incomplete fossil record exists. However, accurate interpretation of carotenoid-derived biomarkers requires detailed knowledge of the carotenoid inventories of contemporary phototrophs and their physiologies. Here we report two distinct patterns of fossilized C40 diaromatic carotenoids. Phanerozoic marine settings show di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 85 publications
3
25
0
Order By: Relevance
“…In broad terms, this is in agreement with a strikingly large variation of bacterial hopanes over eukaryotic steranes observed throughout the Ediacaran (Brocks et al, 2017;Pehr et al, 2018;van Maldegem et al, 2019), which led to the suggestion that on regional scales primary productivity was likely modulated by local determinants such as nutrient supply (Pehr et al, 2018). It is also consistent with distributions of carotenoid pigments (Cui et al, 2020).…”
Section: Nitrogen Isotopes and Nutrient Assimilation In Surface Waters: Cyanobacteria And Algaesupporting
confidence: 83%
“…In broad terms, this is in agreement with a strikingly large variation of bacterial hopanes over eukaryotic steranes observed throughout the Ediacaran (Brocks et al, 2017;Pehr et al, 2018;van Maldegem et al, 2019), which led to the suggestion that on regional scales primary productivity was likely modulated by local determinants such as nutrient supply (Pehr et al, 2018). It is also consistent with distributions of carotenoid pigments (Cui et al, 2020).…”
Section: Nitrogen Isotopes and Nutrient Assimilation In Surface Waters: Cyanobacteria And Algaesupporting
confidence: 83%
“…strain PCC 7002 and relates species, which synthesize renierapurpurin (XIX) as an intermediate in the biosynthesis of the cyanobacterial carotenoid χ,χ‐caroten‐18,18’‐dioic acid (XXV), otherwise known as synechoxanthin, via the intermediates XXI, XXII, and XXIV (Graham & Bryant, 2008; Graham, Lecomte, & Bryant, 2008). Further research has confirmed production of renieratene and traces of isorenieratene from these strains (Cui et al., 2020). Studies of the presence of synechoxanthin in Synechococcus sp.…”
Section: Resultsmentioning
confidence: 79%
“…French et al (2020) Graham, Lecomte, & Bryant, 2008). Further research has confirmed production of renieratene and traces of isorenieratene from these strains (Cui et al, 2020). Studies of the presence of synechoxanthin in Synechococcus sp.…”
Section: Euxinic Photic Zone or Not?mentioning
confidence: 79%
“…2). Renieratane and renierapurpurane are carotenoid biomarkers sourced from numerous strains of cyanobacteria (31,32) and high (ren+rnp)/iso ratios, as observed in the upper CIE, are typical of Phanerozoic lacustrine settings with low sulfate inventories (33). Increases in chlorobactane and okenane carotenoid biomarkers suggest expansion of anoxic green-pigmented GSB and PSB layers in microbial mats beneath surficial cyanobacterial layer(s) (Fig.…”
Section: Sea-level Fall Resulted In Microbial Mat Emergence and Ecologicalmentioning
confidence: 96%